Pristojnost v nepogodbenih odškodninskih sporih - Galič, Aleš (Pravni letopis, 2012)
Both Slovenian national law (International Private Law Act concerning the international jurisdiction and Civil Procedure Act concerning territorial jurisdiction) as well as the Brussels I Regulation provide for a special (elective) jurisdiction for matters relating to tort. The claimant has the option of suing the defendant in the courts in which a harmful event occurred or in the place in which the damage is suffered. However, the latter option is only available in the place where harmful effects upon the person who was the immediate victim is a direct result of the harmful event. A restrictive approach is necessary in order to prevent forum shopping and to prevent a practically unlimited opening of a forum actoris. Such a restrictive approach is necessary in regard to disputes concerning pure economic loss as well, although particularly in such cases it is difficult to locate the place, where the damage occurred (and to differentiate it from the centre of the victim's economic interests). Furthermore, the "doctrine of mosaic" concerning claims arising out of violation of personality rights in media, is also discussed, both with regard to traditional as well as modern media. In the last chapter, the author discusses certain issues concerning subject matter jurisdiction and calculation of the amount in controversy in case of joinder of claims for non-pecuniary and pecuniary damage.
Keywords: odškodninska odgovornost; pooblastila; pristojnosti; reševanje; sodišča; spori